Audrey : more than an icon [videorecording (DVD)] - Somers, Alex (Bohemia, 2020)
"Actress, humanitarian, film and fashion icon, Audrey Hepburn was undoubtedly one of the greatest legends from the Golden Age of Hollywood. But who was the real Audrey Hepburn? Malnourished as a child, abandoned by her father, and growing up under Nazi occupation in Holland, Hepburn faced a life-long battle with the traumas of her past, which thwarted her dreams of becoming a ballet dancer, and cast a shadow over her personal life. yet she found inner peace, using her superstardom for good as a global ambassador for UNICEF, and bringing her life full circle: first as a victim of war, then a source of relief to millions. A hybrid of rare archve, cinematic dance sequences, and intimate interviews with those who knew her best, this film brings a truly extraordinary woman to life, who stands as a testament to the power of love and forgiveness." -- adapted from container.